2016
DOI: 10.1590/s1806-92902016000300006
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour, heart rate, and heart rate variability in pigs exposed to novelty

Abstract: -In the present study, we investigated behavioural responses and determined parameters of heart rate variability (HRV) to elucidate a relative activation of autonomic nervous system (ANS) during baseline (10 min) and in response to potentially stressful situations (10 min) in two pig breeds and sexes. Gilts (n = 21) and barrows (n = 9) of the Landrace × Yorkshire (LY; n = 15) and Landrace/Yorkshire × Landrace/Duroc (LYLD; n = 15) breeds were subjected to a novel object test (NOT) and a novel arena test (NAT). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…In that study, pigs were selected from a single farm and control pigs were selected from the pens with no tail-biting outbreaks, which could explain the inconsistency between the studies. When assessing at the novel-object and the novel-arena test situations, it was interesting to see that, although the behaviour responses were indicative of emotional experiences and the cardiovascular responses were induced (Zupan et al, 2012(Zupan et al, , 2016, no difference in the activation of HPA-axis was found. We found similar results in pigs of different breeds and sexes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In that study, pigs were selected from a single farm and control pigs were selected from the pens with no tail-biting outbreaks, which could explain the inconsistency between the studies. When assessing at the novel-object and the novel-arena test situations, it was interesting to see that, although the behaviour responses were indicative of emotional experiences and the cardiovascular responses were induced (Zupan et al, 2012(Zupan et al, , 2016, no difference in the activation of HPA-axis was found. We found similar results in pigs of different breeds and sexes.…”
Section: Discussionmentioning
confidence: 99%
“…We documented that the activity of the autonomic nervous system, especially the suppression of parasympathetic tone, indicates that some pigs may have a dysfunctional autonomic regulation (Zupan et al, 2012). Additionally, the results indicated that in tail-biting pens, pigs of different sexes and breeds possess different autonomic flexibility (Zupan et al, 2016). In this paper, we tested pigs in a human-response test, a novel object test, a novel arena test, and during transportation and assessed the activation of stress-axis, using a non-invasive method to measure salivary cortisol concentrations.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations